Web-Based E-Tatib Information System Case Study at State Vocational High School 1 Jabon Sidoarjo Sistem Informasi E-Tatib Berbasis Web Studi Kasus di SMK Negeri 1 Jabon Sidoarjo - Jamal Hasan; Mochamad Alfan Rosid; Ade Eviyanti; Hamzah Setiawan (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This research was conducted because the need for an increasingly stringent Standard Operating Procedure (SOP) in the industrial world. With the existence of SOPs in the world of education industry, of course, they have to match the needs according to existing standards. SMK Negeri 1 Jabon Sidoarjo formed a Team of Rules (Tatib) which implemented SOPs in accordance with Industrial World standards. Handling related to Tatib is still done manually using a book. Of course, with manual recording, efficiency in processing time and reporting is constrained if needed in a short time. The recording process begins with the admin entering the master data required by the information system, then the teacher enters the recording of student violations. The final process for the Counseling Guidance (BK) team can see the number of range points that have been stored and will then make reports outside the information system. That way the process makes the work of the BK team more accurate and faster